The Conconi test: a controversial concept for the determination of the anaerobic threshold in young rowers - Bourgois, J.; Vrijens, J. (International Journal of Sports Medicine, 1998)
In order to examine the validity of Conconi's heart rate threshold (ATHR) during rowing ergometry, in accordance with the new recommendations of Conconi, ten young rowers (age 17.5 [SD 1.7] years; height 182.5 [SD 5.9]cm; body mass 77.0 [SD 10.6] kg) were submitted - at random and within 48-72 h - to two progressive incremental exercise tests on a rowing ergometer. In the first test, the heart rate threshold (ATHR) was determined during a ramp-like incremental test. In a second test, the lactate method (150W + 50W x 3 min(-1)) was used to determine the 4 mmol x l(-1) threshold (AT4) and the individual anaerobic threshold (IAT). Subsequently, each subject performed within 48-72 h after the second progressive incremental exercise test a 30 min prolonged exercise test (PET) at the power output corresponding to ATHR to demonstrate whether or not a steady state in blood lactate concentration ([La-]bSS) could be maintained. Friedmann's analysis of variance, Wilcoxon signed ranks test and Spearman rank correlation coefficient (rs) were used as statistical tools. Significant lower values for power output (p < 0.01 ) and heart rate (HR) (p < 0.01) were found at IAT as compared to AT4 and ATHR. No relationships were found between ATHR on the one hand and AT4 and IATon the other hand, neither for power output (rs=0.27 and -0.09), nor for HR (rs=0.08 and -0.08). Coefficients of correlation between AT4 and IAT were respectively 0.68 (p < 0.05) for power output and 0.79 (p < 0.01) for HR. During PET only four out of 10 rowers reached the target time of 30 min at ATHR power output and only one rower showed a lactate steady state. From our results we can conclude that power output at ATHR is overestimated and cannot be used for the prescription of endurance training in rowing. The ATHR does not reflect the anaerobic threshold and is therefore not relevant for monitoring continuous endurance training in rowing.